Edgar H. Schein The Artistry of a Reflexive Organizational Scholar-Practitioner - Coghlan, David (Routledge Studies in Organizational Change & Development, 2024)
The contribution of Edgar H. Schein to the field of management, organisation studies and applied behavioural science is both extensive and deep. For almost 70 years, he has creatively and systematically shaped theory and practice in areas including organisation development and change, career dynamics, the cultural dynamics of complex systems, leadership, process consultation and the clinical inquiry/research paradigm. He has written extensively on the process of organisational change and framed the construct of the clinical approach to research. With such an extensive corpus over such a long period, Schein has been termed a "transcendent thought leader" and it is in this spirit that a volume exploring his work offers a contribution how scholars and practitioners can come to understand their engagement in organisations. This singular volume adopts a reflective perspective on the work of Edgar Schein as a social scientist and shows how he developed his craft as an engaged organisational scholar-practitioner through reflexive attention to his experience in working with managers and organisations and generating knowledge out of action. The intended contribution is both to present Schein's work to students and scholars of organisation studies and to offer a reflexive methodological framework to engage scholar-practitioner in any field.